2009
DOI: 10.1016/j.compind.2009.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Supporting shop floor workers with a multimedia task-oriented information system

Abstract: This paper reports the work carried out as part of an industrial research project sponsored by a major telecommunication industry based in the UK. The main aim of the research was to investigate the extent to which a multimedia-based information system, developed for shop floor workers, has contributed to the increased efficiency and productivity of manufacturing operations. To achieve this, the work has focused on the design and execution of the evaluation of the system. Due to the fact that the direct impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…This model looked at various types of knowledge and their effects on different task units. In similar study Tjahjono (2009) found out multi-media-based information system increased efficiency and productivity of manufacturing operations. Using three industry categories Islam and Shazali (2011) studied degrees of skills, favorable working environment and R&D on manufacturing productivity of labor-intensive industries.…”
Section: Literature Reviewmentioning
confidence: 84%
See 1 more Smart Citation
“…This model looked at various types of knowledge and their effects on different task units. In similar study Tjahjono (2009) found out multi-media-based information system increased efficiency and productivity of manufacturing operations. Using three industry categories Islam and Shazali (2011) studied degrees of skills, favorable working environment and R&D on manufacturing productivity of labor-intensive industries.…”
Section: Literature Reviewmentioning
confidence: 84%
“…There have been numerous studies been carried out to identify the most influential factors affecting productivity including quality (Lee et al, 2007;Terziovski, 2006), knowledge (Kollberg and Elg, 2011), investment (Mawdesley and Al-Jibouri, 2010), equipment losses (Shirose, 1996), maintenance (Bamber et al, 1999;Ahuja and Khamba, 2008) , working methods (Tjahjono, 2009) and labor quality (San et al (2008). Based on the data collected from UK construction firms Mawdesley and Al-Jibouri (2010) identified five dominant factors including investments in planning and control.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Figure 5.3 serves to highlight the challenges surrounding levels of analysis that must be resolved to effectively advance TTF research. For example, there would seem to be some value in improving our explanations of how individual level TTF Dishaw and Strong (1999), Klopping and McKinney (2004), Norzaidi et al (2009Norzaidi et al ( , 2007, Tjahjono (2009 (continued) Dishaw and Strong (1998a, b, 1999, Goodhue et al (1997), Goodhue and Thompson (1995), Klopping and McKinney (2004), Kositanurit et al (2006), Lam et al (2007), Huang (2008, 2009), Nance and Straub (1996), Norzaidi et al (2009Norzaidi et al ( , 2007 leads to organizational performance benefits. The literature has, thus far, tended to rely on user perceptions of performance such as perceptions of whether a technology improves productivity.…”
Section: Summary Frameworkmentioning
confidence: 93%
“…Besides, Dishaw et al 12 suggested TAM and TTF models combined that demonstrated task -technology fit to have a significant impact on perceived usefulness. Based on TTF, TAM and TTF models combined and some studies such as Norzaidi et al (2009), Tjahjono (2009), Chang (2008), Wu et al (2007), Klopping and McKinney (2004), Dishaw and S trong (1999), Goodhue (1995) 9,10,19,[29][30][31][32][33] hypothesis H2 is stated as follows: H2: The task -technology fit has a positive effect o n the perceived usefulness in ERP environment. Based on three theories, namely TAM and TTF models combined, ECM (Expectation-Confirmation Model) 14 and DeLone and McLean IS Success Model (2013) 2 , this study developed the hypothesis H3.…”
Section: Perceived Usefulnessmentioning
confidence: 99%